2019
DOI: 10.1039/c9ra04604f
|View full text |Cite
|
Sign up to set email alerts
|

A multicomponent, facile and catalyst-free microwave-assisted protocol for the synthesis of pyrazolo-[3,4-b]-quinolines under green conditions

Abstract: A facile, swift and ecofriendly microwave-assisted multi-component/one-pot protocol is designed for the synthesis of novel pyrazolo-[3,4-b]-quinolines at ambient temperature in aqueous ethanol as a reaction medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The stated protocol reveals an efficient strategy to produce fused pyrazoloquinolines in good to excellent yields with good functional group tolerance. In 2019, a very similar approach was demonstrated by Jonnalagadda and co-workers [134] with 5-amino-3-methyl-1-phenylpyrazole (150), aldehyde 5, cyclic 1,3-diketone like dimedone (6a) under microwave irradiation in a solvent mixture of water and ethanol at 50 °C. The constructed pyrazolo [3,4-b]…”
Section: Quinolinesmentioning
confidence: 72%
See 1 more Smart Citation
“…The stated protocol reveals an efficient strategy to produce fused pyrazoloquinolines in good to excellent yields with good functional group tolerance. In 2019, a very similar approach was demonstrated by Jonnalagadda and co-workers [134] with 5-amino-3-methyl-1-phenylpyrazole (150), aldehyde 5, cyclic 1,3-diketone like dimedone (6a) under microwave irradiation in a solvent mixture of water and ethanol at 50 °C. The constructed pyrazolo [3,4-b]…”
Section: Quinolinesmentioning
confidence: 72%
“…They are also promising antiviral, antiulcer, anxiolytic, antiherpes agents [115][116][117][118][119]. Similarly, pyrazolo-pyridines are found to be potent antibacterial (131), cytotoxic (132), antiproliferative (133) and antimalarial (134) agents (Figure 10) [120,121].…”
Section: Fused Pyridinesmentioning
confidence: 99%
“…In addition, Jonnalagadda S. B. et al. reported that microwave irradiation could also facilitate the preparation of pyrazolo[3,4‐ b ]quinoline derivatives in high yield without catalysts [18] . However, the above protocols, although successful, have some inherent limitations, such as high reaction temperatures, toxic noble metal catalysts, longer reaction times, harsh conditions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…MW induces the growth of oscillation excitation and mass transference in a microwave environment, which produces vigorous heating in reaction vessels, an alternative energy source of chemical reaction for enhanced reaction rate (Polshettiwar and Varma, 2008). Furthermore, the MW technique has attracted considerable interest in organic synthesis due to the higher selectivity, improved product yield, and atom economy, which reduce the by-product generation compared to conventional thermal heating techniques (Khumalo et al, 2019). Therefore, MW-mediated organic synthesis is the preferred green method over unconventional to classical thermal processes for the rapid synthesis of a series Graphical Abstract | Synthesis of Fictionalized 1,4-Dihydropyridines Under Microwave Irradiation and Aqueous Conditions.…”
Section: Introductionmentioning
confidence: 99%